Sintese van metiel-O-[beta]-D-glukopiranosiel-(1[pyltjie]2)-{O-[alfa]-L-Rhamnopiranosiel-(1[pyltjie]6)}-[alfa]-D-glukopiranosied - Hansmann, C. F.(Chris Friedriech) (Stellenbosch : Stellenbosch University, 2012)
Op titelblad verskyn [pyltjie] as die simbool pyltjie.